Pengaruh Kecerdasan Intelektual, Kecerdasan Emosional dan Kecerdasan Spiritual Terhadap Pemahaman Akuntansi - Laksmi, Rizky Ardewi; Sujana, I Ketut (E-Jurnal Akuntansi; Vol 21 No 2 (2017), 2017)
Accounting education in college is intended to educate students to work as a professional accountant who has knowledge in accounting. Understanding the science of accounting requires knowledge of the fundamentals of accounting. These accounting basics are used as a guide to understanding all accounting practices and theories. Understanding of accounting is the process or way of accounting students in understanding accounting courses which is can be influenced by intellectual intelligence, emotional intelligence and spiritual intelligence . The purpose of this study is to determine the effect of intellectual intelligence, emotional intelligence and spiritual intelligence to the understanding of accounting at students majoring in accounting class of 2014 non-regular bachelor program in Faculty of Economics and Business Udayana University. Determination of sample in this research is done by probability sampling technique. Data collection was done by distributing questionnaires to students majoring in accounting class of 2014 non-regular bachelor program in Faculty of Economics and Business Udayana University directly as respondents. Data analysis technique used in this research is multiple linear regression. The results showed intellectual intelligence and spiritual intelligence affect the understanding of accounting students majoring in accounting class of 2014 non-regular bachelor program in Faculty of Economics and Business Udayana University, while emotional intelligence does not affect the understanding of accounting students majoring in accounting class of 2014 non-regular bachelor program .